(untitled) (LEGAL DIALOGICA, 2025)
This study explores the phenomenon of illegal street racing involving teenagers and students in Makassar, as a form of social crime influenced by economic factors, self-identity search, and the desire for recognition. This activity has negative impacts on society, including accidents, material losses, and security disturbances. The research also examines legal aspects and law enforcement related to illegal racing, as well as the main factors contributing to its occurrence. Findings indicate that weak social control, family oversight, and lack of official facilities encourage the continuation of illegal racing. In conclusion, preventive measures and strict law enforcement are essential to reduce such activities. Recommendations include enhancing collaboration among government institutions, police, schools, and communities to strengthen supervision and provide official facilities to curb illegal street racing. Abstrak: Penelitian ini membahas fenomena balap liar yang melibatkan remaja dan pelajar di Kota Makassar, sebagai bentuk kejahatan sosial yang dipengaruhi oleh faktor ekonomi, pencarian jati diri, dan ambisi mendapatkan pengakuan. Fenomena ini memiliki dampak negatif bagi masyarakat, termasuk risiko kecelakaan, kerugian materil, dan gangguan keamanan. Penelitian ini juga mengeksplorasi aspek hukum dan penegakan hukum terkait balap liar, serta faktor-faktor penyebab utama terjadinya kegiatan tersebut. Temuan menunjukkan bahwa kurangnya kontrol sosial, pengawasan keluarga, dan fasilitas resmi turut memperkuat praktik balap liar. Kesimpulannya, tindakan preventif dan penegakan hukum yang tegas diperlukan untuk mengurangi keberlangsungan kegiatan tersebut. Saran yang diberikan adalah meningkatkan kolaborasi antara institusi pemerintah, kepolisian, sekolah, dan masyarakat untuk memperkuat pengawasan dan menyediakan fasilitas resmi agar kegiatan balap liar dapat diminimalisir.